2021
DOI: 10.1002/adfm.202104482
|View full text |Cite|
|
Sign up to set email alerts
|

From Groundwork to Efficient Solar Cells: On the Importance of the Substrate Material in Co‐Evaporated Perovskite Solar Cells

Abstract: Vacuum-based deposition of optoelectronic thin films has a long-standing history. However, in the field of perovskite-based photovoltaics, these techniques are still not as advanced as their solution-based counterparts. Although high-efficiency vacuum-based perovskite solar cells reaching power conversion efficiencies (PCEs) above 20% are reported, the number of studies on the underlying physical and chemical mechanism of the co-evaporation of lead iodide and methylammonium iodide is low. In this study, the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 117 publications
6
74
1
Order By: Relevance
“…[24,42,43] Recently, Abzieher et al showed the advantage of using organic semiconductors as substrates for the vacuum processing of methylammonium lead iodide (MAPI) films. [44] The hydrophobic surface of organics favors the crystallization and orientation of the perovskite film, as opposed to polar metal oxide surfaces, confirming previous observations. [45][46][47] Interestingly, they found that a very thin (<3 nm) undoped film of 2,2',7,7'-tetra(N,N-di-p-tolyl)amino-9,9spirobifluorene (Spiro-TTB) can be employed to ensure ohmic contact between ITO and the MAPI absorber layer, leading to very efficient solar cells.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…[24,42,43] Recently, Abzieher et al showed the advantage of using organic semiconductors as substrates for the vacuum processing of methylammonium lead iodide (MAPI) films. [44] The hydrophobic surface of organics favors the crystallization and orientation of the perovskite film, as opposed to polar metal oxide surfaces, confirming previous observations. [45][46][47] Interestingly, they found that a very thin (<3 nm) undoped film of 2,2',7,7'-tetra(N,N-di-p-tolyl)amino-9,9spirobifluorene (Spiro-TTB) can be employed to ensure ohmic contact between ITO and the MAPI absorber layer, leading to very efficient solar cells.…”
Section: Introductionsupporting
confidence: 88%
“…As previously observed by us and others, co-evaporated MAPI films crystallize in a cubic perovskite phase at room temperature (space group Pm-3m), with only a minor contribution from a residual PbI 2 phase. [44,49] Devices were prepared on ITO-coated glass substrates with the following device configuration: HTL (x nm)/MAPI (500 nm)/C60 (25 nm)/BCP (8 nm)/Ag (100 nm) where BCP is bathocuproine and the HTL is N4,N4, N4 0 0 ,N4 0 0 -tetra([1,1 0 -biphenyl]-4-yl)-[1,1 0 :4 0 ,1 0 0 -terphenyl]-4,4 0 0diamine (TaTm), with thickness varying from 2 to 10 nm. Details of the device fabrication are reported in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…In the inverted perovskite solar cell, the p-type polymers and p-type metal oxides are widely fabricated on top of the ITO/glass substrates with a post-thermal annealing process at about 100 °C. The high-quality perovskite crystalline thin films can be fabricated by using the two-step spin coating method with an interdiffusion process [ 71 , 72 , 73 ], the one-step spin coating method with a washing-enhanced nucleation (WEN) process [ 74 , 75 , 76 ] and the vacuum thermal co-evaporation technique [ 77 , 78 , 79 ]. The organometal trihalide perovskite can be CH 3 NH 3 PbI 3 (MAPbI 3 ), CH(NH 2 ) 2 PbI 3 (FAPbI 3 ) and Cs x (MA y FA 1−y ) 1−x Pb(I z Br 1−z ) 3 , mainly due to the low absorption bandgap [ 80 , 81 , 82 ], large absorption coefficient [ 83 , 84 , 85 ], small exciton binding energy [ 86 , 87 , 88 ], long exciton (carrier) lifetime [ 89 , 90 , 91 ] and high carrier mobility [ 92 , 93 , 94 ].…”
Section: Working Mechanisms Of Perovskite Solar Cellsmentioning
confidence: 99%
“…The employed all-evaporated layer stack sequence ITO/spiro-TTB/CH 3 NH 3 PbI 3 /C 60 /BCP/Au was introduced in an earlier work as a highperformance, low-hysteresis architecture with good short-term stability and reproducibility (see Figures S8-S10). 117 Champion minimodules with an aperture area of 4.0 cm 2 (GFF of 96%) demonstrate PCEs as high as 18.0% with a fill factor (FF) of…”
Section: Efficient Upscaling Of All-laser-scribed Allevaporated Perov...mentioning
confidence: 99%